2000
DOI: 10.1074/jbc.275.25.19306
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Nerve Growth Factor-induced Terminal Differentiation by ret Oncogene Involves Perturbation of Nuclear Translocation of ERK

Abstract: Oncogenic variants of the receptor tyrosine kinase, Ret, cause formation of tumors of neuroendocrine derivation in the multiple endocrine neoplasia type 2 and, thus, likely interfere with antiproliferative and/or differentiative extracellular signals. Here we took advantage of two rat pheochromocytoma-derived cell lines (PC12/MEN2A and PC12/MEN2B) to investigate whether Ret-induced nerve growth factor (NGF) unresponsiveness might involve impairment of ERK signaling. In fact, these cells, stably transfected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…This explanation does not necessarily explain the mechanism by which MKP-3 augments TNF-a gene expression unless MKP-3 was constitutively active. One study has shown, however, that a catalytically inactive mutant MKP-3 can bind to ERK and retain it in the cytoplasm, thus preventing ERK translocation to the nucleus (46). Although MKP-3 can be present in nonstimulated cells, we do not believe this to be the case in human monocytes because our data demonstrate that MKP-3 expression increases in a time-dependent manner after exposure to asbestos.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This explanation does not necessarily explain the mechanism by which MKP-3 augments TNF-a gene expression unless MKP-3 was constitutively active. One study has shown, however, that a catalytically inactive mutant MKP-3 can bind to ERK and retain it in the cytoplasm, thus preventing ERK translocation to the nucleus (46). Although MKP-3 can be present in nonstimulated cells, we do not believe this to be the case in human monocytes because our data demonstrate that MKP-3 expression increases in a time-dependent manner after exposure to asbestos.…”
Section: Discussionmentioning
confidence: 82%
“…Cells expressing the wildtype MKP-3 expression vector had a significant decrease in luciferase activity, while cells expressing the mutant MKP-3 (C293S) had a partial recovery of the ELK-1 luciferase activity that remained below baseline ( Figure 4D). The fact that the mutant MKP-3 did not salvage ERK activation is not surprising, considering the fact that the amino-terminal, noncatalytic domain binds to the ERK and retains it in the cytoplasm regardless of whether ERK is phosphorylated (21,46,47). In particular, one study has demonstrated that overexpression of a catalytic mutant MKP-3 vector prevents downstream ERKmediated gene expression (21).…”
Section: Mkp-3 Regulates Erk Map Kinase Activation In Human Monocytesmentioning
confidence: 95%
“…Complementary DNAs were generated from total RNA by using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems) (25). The resulting cDNA samples were subjected to 10 cycles of polymerase chain reaction (PCR) amplification followed by real-time PCR using the TaqMan PreAmp Master Mix Kit Protocol (PN 4366127; Applied Biosystems).…”
Section: Polymerase Chain Reaction Analysismentioning
confidence: 99%
“…GRB7 or 10 binding (Y905) has also been linked to activation of this pathway 82. In some cell types, RET mediated activation of RAS dependent pathways can result in cellular differentiation,81 while in other cell types, RET activation may actually block RAS induced differentiation by preventing nuclear translocation of ERK and induction of immediate early gene transcription 83…”
Section: Ret Downstream Signallingmentioning
confidence: 99%